Losing trust: Processes of vaccine hesitancy in parents' narratives - Nurmi Johanna; Jaakola Joni (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Lack of trust is central in becoming hesitant towards vaccines, but research on vaccine hesitancy lacks detailed examination of the processes of losing trust. Based on ethnographic interviews with 38 parents in Finland, we explore how and why they have lost their trust in vaccination. We identified two paths to losing trust in vaccination. One was connected to mistrust - a cumulating suspicious attitude toward vaccines and related institutions. The other was associated with distrust - a more sudden loss of trust. We identified four ideal type narratives of losing trust: the activist, the hesitant, the disillusioned and the negotiator. The narratives of the activist and the hesitant were connected to mistrust. The activists were certain of their vaccination decisions whereas the hesitant parents were not. The narratives of the disillusioned and the negotiator were connected with distrust. The disillusioned parents had lost their trust due to adverse effects of vaccination and a lack of institutional support. The negotiators suspected adverse effects and were less certain about their decisions. The article provides insight into the ways in which people lose trust in vaccination, which is crucial for supporting trusting relationships between vaccine-advocating institutions and the publics.